A Short Study on Mary Gilmore with Special Reference to Socialistic Views (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
in common socialism is assumed such economic system in which industries are owned by the workers in place of private owners. It prefers develop social consciousness among mass people evolving socialist region. The socialist writers consider to focus on suffering of oppressed class or weaker section in our societies. Lots of writer are there all over world who reveal in vivid what they witness in their contemporary society in sense of socialistic views. Australian writer Mary Gilmore was such type of writer who noticed suffering of oppressed class people as well as wild animals. She imagined herself as a member of such downtrodden class. Whenever she found scope Mary Gilmore explored such theme through her writings. My short study will try to focus on how Mary Gilmore’s views in sense of socialism as a lover of mankind affected in her writings.